Adaptation of Returned Political Prisoners and Exiles in Soviet Lithuania: Experiences, Strategies, Resources - Šutinienė, Irena (Genocidas ir rezistencija, 2022)
Based on analysis of memories of the repressed people presented in various forms (published memoirs, written and narrated life stories, data of autobiographical surveys carried out by the Genocide and Resistance Research Centre of Lithuania), the article discusses the aspects related to (re)integration of returned deportees and political prisoners in Soviet Lithuania. The typical experiences and trajectories of adaptation process, strategies and resources used, and some of the social factors of adaptation are examined.The most evident socio-demographic factor in the adaptation of the repressed is their age which is related to different socialisation conditions of the age cohorts. A large proportion of the oldest age cohort (born around 1930 and earlier) found themselves in a lower social position than before the arrest or exile, was forced to work in lower-skilled jobs and live in more difficult material conditions. But the cultural capital of this generation was partly passed on in families and, according to the children’s testimony, affected the motivation of the children’s generation to aspire to higher social positions. Younger people had slightly better adaptation opportunities. Part of the cohort born around 1931–1944 could already acquire an education and a profession in the Soviet period (either in exile or after their return to Lithuania), though under more difficult conditions than other groups of society. Most of those who were born after the war (in 1945 and later) became socialised and entered adult life after Stalinism and suffered even less discrimination in occupational and educational settings. As a result, some younger people managed to achieve quite high social positions. But opportunities of this group were limited by their lower material status of family compared to the rest of the society, by fewer social ties, not all of them managed to overcome discriminatory restrictions, therefore, some of the younger people were only able to take up blue-collar professions or unskilled jobs.Among the strategies used by the repressed to overcome the barriers to adaptation caused by discrimination, the most prevalent in terms of quantity is the use of social support of social networks. Other strategies that were less likely to be effective in these situations included concealing the fact of repression, giving bribes to administrative officials, and complaining and petitioning authorities at the national or Soviet Union level. Networks of both close and distant and weak social ties were the most important social resource for the adaptation of the repressed in Soviet Lithuania. Networks of close social ties (family, relatives, close friends and people who had experienced repression) provided all kinds of support – material, emotional, value-based and transmission of memory. Weaker networks provided mainly material assistance (such as helping to get a job or to find housing), and their role in the adaptation process shows that the regime did not succeed in completely breaking people’s trust, as there were people in many groups of society and institutions who were not afraid to help the repressed.Analysed memories also highlight specific motivational and psychological resources for adaptation typical for this group of people, such as the motivation to learn and to achieve a higher social status, which is stronger than that of any other group in the society as a result of the repressive experiences, together with qualities such as perseverance, resilience, occupational and professional skills acquired during the repression, and patriotic as well as moral values. Nevertheless, even overcoming of the barriers to adaptation and reduction of discrimination in the late Soviet period, did not provide the repressed with the feeling of full integration. Neither innocence of these people was recognised, nor the responsibilityof those who had repressed them, and discrimination and stigmatisation of the repressed and their families in institutions and also part of the society continued. It was even reinforced by the silence surrounding their experiences. It is no coincidence, therefore, that in the recollections of the returnees, the experiences of life in Soviet Lithuania are often described as “the second exile” and the feeling of “the marked people” recur throughout the Soviet period. Most of them pointed out that they stopped feeling “second-rate” people only after their rehabilitation in 1989, when their innocence and experiences were recognised, and they became important participants of historical changes. However, the sense of a “marked” identity of an exile is still present among some of them even after the Soviet period.
Keywords: Soviet Lithuania; political prisoners; deportees; deportations; integration